Public health critical race praxis at the intersection of traffic stops and injury epidemiology - Michael Dolan Fliss; Frank R. Baumgartner; Paul Delamater; Steve W. Marshall; Charles Poole; Whitney Robinson (BMC, 2022)
Abstract Background Law enforcement traffic stops are one of the most common entryways to the US justice system. Conventional frameworks suggest traffic stops promote public safety by reducing dangerous driving practices and non-vehicular crime with little to no collateral damage to individuals and communities. Critical frameworks interrogate these assumptions, identifying significant individual and community harms that disparately impact Black, Indigenous, and People of Color (BIPOC) and low-income communities. Methods The Public Health Critical Race Praxis (PHCRP) and multi-level frameworks from community anti-racist training were combined into a structured diagram to guide intervention and research teams in contrasting conventional and critical perspectives on traffic stops. The diagram divides law enforcement and drivers/residents as two separate agent types that interact during traffic stops. These two agent types have different conventional and critical histories, priorities, and perspectives at multiple levels, including individual, interpersonal, institutional, and cultural levels. Conventional solutions (identifying explicitly racist officers, "meet-a-cop" programs, police interaction training for drivers) are born from conventional frameworks (rewarding crime prevention regardless of cost, the war on drugs saves lives, driver behavior perfectionism). While conventional perspectives focus on individual and interpersonal levels, critical perspectives more deeply acknowledge dynamics at institutional and cultural levels. Critical solutions may be hard to discover without critical frameworks, including that law enforcement creates measurable collateral damage and disparate social control effects; neighborhood patrol priorities can be set without community self-determination or accountability and may trump individual and interpersonal dynamics; and the war on drugs is highly racialized and disproportionally enforced through traffic stop programs. Conclusions Traffic stop enforcement and crash prevention programs that do not deeply and critically consider these dynamics at multiple levels, not just law enforcement-driver interactions at the individual and interpersonal levels, may be at increased risk of propagating histories of BIPOC discrimination. In contrast, public health and transportation researchers and practitioners engaged in crash and injury prevention strategies that employ law enforcement should critically consider disparate history and impacts of law enforcement in BIPOC communities. PHCRP, anti-racism frameworks, and the included diagram may assist them in organizing critical thinking about research studies, interventions, and impacts.